Policy Analysis of Career Guidelines at The High School Level for Physics Education Program for West Sumatera and North Sumatra Regions - Zakirman Zakirman; Wienda Gusta; Chichi Rahayu (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2021)
The guidance of career counseling can lead, provide insight and knowledge about the world of work and current issues in facing competition in the world of work. The magnitude of the impact caused by the counseling career counseling program, making the educational policy stakeholders at a university institution consider the implementation of guidance services to prospective graduates who will compete in the world of work. This type of research is descriptive qualitative and aims to describe the results of the analysis of educational policies that have been taken by several universities regarding career counseling guidance services. The sample universities taken in the research activity were : IAIN Batusangkar, STKIP PGRI Sumatera Barat, Universitas Muhammadiyah Tapanuli Selatan, Institut Pendidikan Tapanuli Selatan, UIN Imam Bonjol Padang, Universitas Negeri Padang, dan Universitas Putra Indonesia YPTK Padang. The instrument for collecting research data is in the form of a questionnaire which is distributed to the leaders and officials of study programs, departments, faculties, and universities/colleges. The results of this study include: report on career counseling guidance policy at the host institution, obstacles faced by the organizer, service impact for graduates, and evaluation of career counseling guidance policy. Based on the analysis that has been done, the counseling guidance program is feasible to be applied by every university in order to create a successful alumni career in the future. Therefore, the leadership and all levels of higher education can work together to create a policy for career counseling guidance services at the university level.